Cold case file : murder in the mountains - Gordon, Olivia (New York : Bearport, 2008)
Tells the story of how forensic science helped to convict Roy Melanson for the 1974 murder of twenty-five-year-old Michele Wallace in the Rocky Mountains.
A disappearance -- The search -- The case goes cold -- The detective -- Getting away with murder? -- NecroSearch -- A new search -- A skull -- Gathering evidence -- The truth at last -- The court case -- Case closed -- Crime solving up close.
Includes bibliographical references (p. 32) and index.
4.6
5-8
Keywords: Melanson, Roy; Wallace, Michele, -- d. 1974.; Melanson, Roy; Wallace, Michele, -- d. 1974.; Melanson, Roy; Wallace, Michele, -- d. 1974.; Cold cases (Criminal investigation) -- Colorado -- Juvenile literature; Missing persons -- Colorado -- Juvenile literature; Murder -- Investigation -- Colorado -- Juvenile literature; Murder -- Colorado -- Juvenile literature; Criminal investigation; Missing persons; Murder; Criminal investigation; Homicide; Missing persons